2012
DOI: 10.2139/ssrn.2127722
|View full text |Cite
|
Sign up to set email alerts
|

Job Demand and Early Retirement

Abstract: Policy initiatives such as increases in the full retirement age implicitly reduce benefits for early retirement. Yet research suggests that those in physically demanding jobs may be particularly adversely affected by such policies. We examine to what extent physical job demand relates to early retirement decisions in a population of aging manufacturing workers. We follow a cohort of approximately 1,500 stably employed male Alcoa employees aged 51-58 in 2001 followed forward to 2008. We use a variety of models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…This finding is very consistent with research showing a strong impact on retirement of physically demanding work (Modrek, & Cullen, 2012) and physical limitations (Belbase et al, 2015), but is one of the first studies to specifically examine the interaction effect.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding is very consistent with research showing a strong impact on retirement of physically demanding work (Modrek, & Cullen, 2012) and physical limitations (Belbase et al, 2015), but is one of the first studies to specifically examine the interaction effect.…”
Section: Discussionsupporting
confidence: 90%
“…Job demands and particularly personal resources may change over time especially toward the end of workers’ careers. Studies that investigated the job demands within these domains have found overall that higher levels of physical effort, work stress, and cognitive demand put workers at risk for earlier retirement (Aaron & Callan, 2011; Modrek & Cullen, 2012; Wahrendorf, Dragano, & Sigerist, 2015; Willis, 2013). Interestingly, jobs that have more cognitive demands tend to be associated with white-collar work and could therefore be associated with much later retirement if demands do not exceed resources (Fisher et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, education does play an important role in type of occupation (such as managerial or physical labour), and men in physically demanding jobs tend to retire early due to health issues (Modrek & Cullen, 2012). We found that partnered women and men were less likely to have decreasing full time work, as compared to mostly full time work.…”
Section: Accepted Manuscriptmentioning
confidence: 68%
“…Each unit increase predicts a one‐fold increase in expenditures above the mean. This score predicts a variety of health outcomes (Handel ; Modrek and Cullen , ; Kubo et al. ), including mortality in higher quintiles (Hamad et al.…”
Section: Methodsmentioning
confidence: 99%